Focused Diagnostic Approach to A Patient with Fever of Unknown Origin (FUO): A Review (BIRDEM Medical Journal, 2013)
Fever of unknown origin (FUO) is a diagnostic challenge for clinicians. Disorders presenting as fever of unknown origin are varied and extensive. Clinicians often find themselves hopeless with a patient with FUO and try to catch a straw by doing every conceivable test and run therapeutic trials in order to diagnose all of the myriad causes of FUO that are in fact part of the differential diagnosis of FUO in general. The main difficulty with diagnostic testing in patients with FUO is that it is unfocused. All disorders have a specific pattern of organ involvement. In a patient with FUO, there are almost always one or more clues from the history, physical examination, or nonspecific laboratory tests that suggest a particular diagnosis or at least limit diagnostic possibilities. It is worthy to remember that fever of unknown origin is more often caused by an atypical presentation of a common entity than by a rare disorder. Thus a focused diagnostic approach can minimize the miseries of both the clinician & the patient. Birdem Med J 2013; 3(1): 27-34 DOI: http://dx.doi.org/10.3329/birdem.v3i1.17124